"They would call me, and I would need to know because it is like life and death": A qualitative examination of the acceptability of smartphone applications designed to reduce mobile phone use while driving. (August 2020) - Oviedo-Trespalacios, Oscar; Vaezipour, Atiyeh; Truelove, Verity; Kaye, Sherrie-Anne; King, Mark
Highlights: Participants identified that the applications could reduce distracted driving. Drivers with maladaptive mobile phone use might not use the applications. Drivers are not comfortable using all the functions of the applications. Future updates need to consider the user to increase uptake of the applications. Abstract: Distracted driving is one of the most prevalent risky behaviours worldwide. Research has highlighted that current approaches to distracted driving based on education and police enforcement have shown low effectiveness. Smartphone applications to reduce distracted driving are an emerging technology with the potential to prevent road crashes. However, recent evidence has shown that the adoption of these applications has been limited. A qualitative study was carried out to investigate the acceptability of smartphone applications that are designed to prevent distracted driving. A total of 35 drivers (57% females) aged 19–44 years ( Me an = 28.43) participated in interviews which explored acceptability constructs for in-vehicle intelligent technology as defined by Regan et al. (2012): usefulness, usability, effectiveness, social acceptability, affordability, and willingness to use the application functions. Generally, drivers perceived that these applications have the potential to increase safety and reduce voluntary and involuntary mobile phone interactions while driving. Nonetheless, it was also found that drivers want to retain some of the functionalities of their mobile phone, such as music playing applications, accessing GPS/maps and being able to interact with certain groups of people through their phones while driving. Finally, barriers to the uptake of the applications among drivers who use their mobile phone while driving are discussed. A frequent barrier that needs to be overcome is the perceived need and pressure to respond to their phone while driving to communicate for work purposes or with people with strong social ties to the driver, for example, a parent or spouse.